ANALISIS TENTANG PENDIDIKAN DAN PELATIHAN TERHADAP PENINGKATAN KOMPETENSI PEGAWAI NEGERI SIPIL DALAM MENGHADAPI MASYARAKAT EKONOMI ASEAN (MEA) - Tanti Kirana Utami (Jurnal Hukum Mimbar Justitia, 2016)
Asean Economic Community (AEC) / AEC (Asean Economic Community) in 2015 is a program that has long been prepared all members of ASEAN which aims to improve the economic stability in the ASEAN region and form the economic area among ASEAN countries is strong. One important aspect that needs to be prepared quickly this nation is the human resources competent civil servants . The program to improve the competence of employees is done through education and training programs training. Education and training of personnel contributed to the increase in productivity , efektitas and organizational efficiency .Â Keywords: Competency Enhancement, Civil Servants, the Asean Economic Community.